2021
DOI: 10.1088/2050-6120/abf424
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime imaging microscopy and time-resolved anisotropy of nanomaterial-induced changes to red blood cell membranes

Abstract: With the use of engineered nano-materials (ENM) becoming more prevalent, it is essential to determine potential human health impacts. Specifically, the effects on biological lipid membranes will be important for determining molecular events that may contribute to both toxicity and suitable biomedical applications. To better understand the mechanisms of ENM-induced hemolysis and membrane permeability, fluorescence lifetime imaging microscopy (FLIM) was performed on human red blood cells (RBC) exposed to titaniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We have previously demonstrated that crystalline silica can interact with and disrupt lipid membranes, which resulted in changes to lipid order in the membrane. This is likely through preferential interactions with phosphatidylcholine (DOPC) phospholipid headgroups ( Pavan et al, 2020 ; Sydor et al, 2021 ; Pavan et al, 2022 ). Because of this our current work utilized 100-nm liposomes composed of DOPC with or without cholesterol that were incubated with crystalline silica for the purpose of detecting silica-induced changes to membrane order.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously demonstrated that crystalline silica can interact with and disrupt lipid membranes, which resulted in changes to lipid order in the membrane. This is likely through preferential interactions with phosphatidylcholine (DOPC) phospholipid headgroups ( Pavan et al, 2020 ; Sydor et al, 2021 ; Pavan et al, 2022 ). Because of this our current work utilized 100-nm liposomes composed of DOPC with or without cholesterol that were incubated with crystalline silica for the purpose of detecting silica-induced changes to membrane order.…”
Section: Resultsmentioning
confidence: 99%
“…Silica has been described to interact with lipid membranes and disrupt them, as measured by lipid order changes ( Sydor et al, 2021 ; Pavan et al, 2022 ). Specifically, we have proposed that nearly free silanol groups on the surface of crystalline silica can interact with phosphatidylcholine headgroup lipids and cause a change in lipid order in membranes ( Pavan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations